Associação do nível de atividade física com a qualidade de vida, estresse e resiliência do professor da educação básica - Cavalcante, Rosilene Vila Nova (2018)
This study aims to associate the level of physical activity with the quality of life, stress phases and resilience scale of teachers who are in effective class regency in the basic education of the Municipality of Ubatã, Bahia. It is a quantitative, descriptive and field research. We used the International Physical Activity Questionnaire (IPAQ), short version, to evaluate the level of physical activity, the Quality of Life Scale (EQV), the Lipp Stress Symptom Inventory (ISSL) (RS) originally created in English by Wagnild and Young, adapted for Brazil by Pesce et al., and a questionnaire to evaluate sociodemographic aspects. For the descriptive analysis of the data, means, deviations and frequencies were run. In the analysis of the inferences, normality tests (kolmogorov-Smirnov), t-test for independent samples, two-way ANOVA were used to compare the two groups (active and insufficiently active) and Chi-Square to evaluate differences between variables qualitative. The results show that 93% of the teachers' network is female, 67.5% are considered active and that there was no association between the dependent variable, physical activity level, with the investigated variables: quality of life, resilience and phases of stress. We suggest for future research an analysis of intervening variables, which may have altered the phenomena, such as characteristics and habits of the population, classification of physical activity, daily routine and displacement.